MAINTAINING ADAB IN THE DIGITAL AGE: STRATEGIES OF AL-FALAH KONGSI PESANTREN IN PRESERVING STUDENT HUMILITY (TAWADU’) - Agus Santoso; Abdul Majid; Nur Farida (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
This study explores the challenges of digitalization within traditional pesantren (Islamic boarding school) education systems, specifically focusing on maintaining students' tawadu’ (humility) amidst the rapid flow of information technology. The research employs a qualitative descriptive method, with data collected through observation, in-depth interviews, and documentation at Al-Falah Kongsi Pesantren, Wonosobo. The subjects include caregivers, teachers (ustadz), and students to obtain a comprehensive view of learning dynamics in the digital era. The findings reveal that the pesantren integrates technology through WhatsApp groups for alternative learning, the use of independent translation applications for the Matan Zubad text, and the utilization of social media as a creative medium for dakwah (proselytizing). However, significant obstacles exist, including technological distractions, limited internet infrastructure, and the risk of diminished focus and adab (etiquette) due to uncontrolled digital exposure. Strategies to preserve student character include intensive personal supervision, strict enforcement of gadget usage hours, and the reinforcement of ethical values through the routine study of classical texts. This study concludes that digital integration is complementary and effective in enhancing learning efficiency as long as it remains directed toward strengthening moral values. The personal relationship between teachers and students, alongside the exemplary behavior of caregivers, remains an irreplaceable and vital instrument in the character-building process.